Investigation of Vandal Behavior of the Social Situation in the Territory in the Period of Destruction - Obolenskaya, A (KnE Life Sciences, 2018)
The article describes modern types and risks of vandalism in cities environment. Vandal activity in cities is steadily increasing (Mursalieva, 2017). New types of vandalism appear in streets of megalopolises, where involvement in crime communications tends to 70%. Surveyed townspeople often do not see anything reprehensible in perfect vandalism, like graffiti and product logos, to use municipal and private property for their messages. Graffiti on a municipal building, trampled lawns, broken garbage bin on the street is not considered something unusual, it’s public goods and it seems to be a draw. Perception of spoiling becomes a habitual norm. However, the alternative consequences for the citizens-spectators and the actors themselves constitute serious risks for socialization, mental and physical health, a sense of well-being. Vandalism is also active as a marketing communication, in which ads are placed in the city’s space without the consent of the owner of the building, which causes anxiety of the owner and users of the premises and the territory as a whole. We analysed more than 3 thousand objects damaged by vandals in the megacity of Yekaterinburg, which is located in the center of Russia and includes 7 districts. 1.5 million residents live in elite housing and old low-budget homes. Even well-protected residential complexes have graffiti. However, in low-density areas there is more graffiti as a criminal communication. Keywords: vandalism, destruction of the social situation, territory, economic of vandalism, economic behavior.